问题
解答题
解方程: (1)x2-2x-1=0. (2)x2+2x-1=0. (3)x2+x-1=0. (4)x2+3x-1=0. (5)x(x+2)=1. (6)5(x-3)2=125. (7)x2+2=2
(8)3(x2-5)=4x. (9)3x2+(x-2)=0. (10)(2x-1)(x+3)=4. (11)x2-3x-4=0. (12)x2-3x-18=0. |
答案
(1)x2-2x=1,
x2-2x+1=2,
(x-1)2=2,
x-1=±
,2
∴x1=1+
,x2=1-2
.2
(2)x2+2x=1,
x2+2x+1=2,
(x+1)2=2,
x+1=±
,2
∴x1=-1+
,x2=-1-2
.2
(3)△=1-4×(-1)=5,
x=
,-1± 5 2
∴x1=
,x2=-1+ 5 2
.-1- 5 2
(4)△=9-4×(-1)=13,
x=
,-3± 13 2
∴x1=
,x2=-3+ 13 2
.-3- 13 2
(5)x2+2x=1,
x2+2x+1=2,
(x+1)2=2,
x+1=±
,2
∴x1=-1+
,x2=-1-2
.2
(6)(x-3)2=25,
x-3=±5,
∴x1=8,x2=-2.
(7)x2-2
x+2=0,3
△=12-4×2=4,
x=
=2
±23 2
±1,3
∴x1=
+1,x2=3
-1.3
(8)3(x2-5)=4x,
3x2-4x-15=0,
(3x+5)(x-3)=0,
∴x1=-
,x2=3.5 3
(9)3x2+(x-2)=0,
3x2+x-2=0
(3x-2)(x+1)=0,
∴x1=
,x2=-1.2 3
(10)(2x-1)(x+3)=4,
整理为2x2+5x-7=0,
(2x+7)(x-1)=0,
∴x1=-
,x2=-1.7 2
(11)x2-3x-4=0,
(x-4)(x+1)=0,
∴x1=4,x2=-1.
(12)x2-3x-18=0,
(x+3)(x-6)=0,
∴x1=-3,x2=6.